Taksonomiczna ocena poziomu rozwoju województw "ściany wschodniej" na tle kraju - Tarka, Danuta (Taxonomic evaluation of the development's level of so called "Eastern Wall Voivodeships" against Poland, 2006)
This paper aims at comparing to what eXtent the 1999 administrative reform has indirectly influenced changes within five years (from 1999 to 2003) in the level of economic and social development of four so called “Eastern Wall Voivodeships”. Two synthetic measures have been used to evaluate and order the objects under consideration: one based on Hellwig’s proposition and the other based on principal component analysis. There have been used 34 diagnostic variables. In 1999 analyzed voivodeships had the lowest values of used measures in Poland. Five years after reform the situation of podlaskie and podkarpackie voivodeships has changed for better in relation to the rest of the country, the positions of two other voivodeships have remained the same.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 571-580